Clinical Cases in Middle-Years Pediatric Dermatology - Lotti, Torello M.; Arcangeli, Fabio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is a concise practical guide designed to facilitate the clinical decision-making process in the management of pediatric skin disease in older children. Dermatologists and general pediatricians who offer primary care to children must be knowledgeable in managing dermatological problems, and this title provides insightful reviews of a number of common and rare dermatologic cases. Clinical cases are a key component in modern medical education, assisting the trainee or recertifying clinician work through unusual scenarios using best practice techniques. Pediatric dermatology is a particularly important discipline in this regard since it is a highly visual subject requiring the reader to describe often very subtle differences in the presentation of patients and define accurately the diagnostic and management criteria on which to base their clinical decision-making. Clinical Cases in Middle-Years Pediatric Dermatology concisely covers how to approach diagnosing and managing patients between 6 and 11 years of age. Each chapter focuses on a particular case and emphasizes how to make an appropriate choice when deciding which diagnostic tool or management strategy would be most suitable. Potential complications are detailed and management tips provided to enable the reader to develop a deep understanding of how approach the care of these patients within their day-to-day clinical practice. This book therefore represents an ideal up-to-date resource for all practitioners who encounter the condition as part of their everyday practice.
A Child With a Pruriginous Symmetrical Rash -- A pediatric patient with photosensitivity -- Acquired pigmented lesion in a 6-year-old child -- Erythematous patch on the antecubital fossa -- Erythematous ulcerated perioral nodule -- Hypopigmented mycosis fungoides in pediatric: serial cases -- Itching And Edematous Lesion Of The Fifth Toe After Caribbean Holiday -- Pediculid: an autosensitization dermatitis developed as an-id reaction to pediculosis infestation -- Unusual pigmentation of skin and hair -- Vaginal bleeding and "café au lait" patches -- Xeroderma Pigmentosum -- A seven-year-old boy with stomatitis, conjunctivitis and dehydration -- A young boy with fever and wide spread pustules -- An erythematous nummular lesion with a centrifugal growth -- Dermatitis, hidradenitis suppurativa -- The Impact of Malnutrition to Pseudomonas aeruginosa Infection in Children -- Asymptomatic papules of the trunk -- Congenital small dimple on the median line of the nose -- Diffuse itchy dermatitis in an eight-year-old girl -- Hyperkeratotic plaques on the extensor extremities and punctate palmoplantar keratoderma in a boy -- Purpuric eruption in a COVID 19 positive child -- Longitudinal Melanonychia In Pediatric -- Pruritic erythematous plaque on the knee -- Scaly itchy lesion of glans penis -- A 10-year-old patient with erosive stomatitis, conjunctival hyperaemia and fever -- A strange dermatitis in a young boy -- A ten-year-old boy with a nodular lesion on the upper lip -- Cutaneous Lesions and Multisystem Inflammatory Syndrome in Children (MIS-C) -- Non-Segmental Vitiligo In 10 Years Old Child -- Acneiform eruption in prepubertal children -- Hair loss in an 11-year-old -- Nail dystrophy in a young boy -- Neurofibromatosis Type 1 With Congenital Pseudarthrosis Tibialis -- Psoriasis Vulgaris in Children with Obesity -- Well defined round nodules of the thigh.
Keywords: Dermatology; Pediatrics; Dermatology; Pediatrics; Skin Diseases; Child; Case Reports